2018
DOI: 10.1111/apt.14955
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: risk of adverse cardiovascular events with proton pump inhibitors independent of clopidogrel

Abstract: There is no clear evidence of an association between PPI monotherapy and increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 75 publications
(366 reference statements)
1
40
0
2
Order By: Relevance
“…Such a possibility can never be excluded no matter how large the sample size of the trial. It is reassuring, however, that the HRs and ORs reported in this trial are lower than the lower end of the 95% CI of the observational data for pneumonia, 23 fracture, 26 cardiovascular disease, 27 chronic renal disease, 16 dementia, 17 and all-cause mortality. 18 Some data suggest adverse events associated with PPI therapy are not seen until after 5 years of therapy 36 and this trial had a mean follow-up of 3 years and a maximum follow-up of 5 years, which was achieved in only a small proportion of patients.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Such a possibility can never be excluded no matter how large the sample size of the trial. It is reassuring, however, that the HRs and ORs reported in this trial are lower than the lower end of the 95% CI of the observational data for pneumonia, 23 fracture, 26 cardiovascular disease, 27 chronic renal disease, 16 dementia, 17 and all-cause mortality. 18 Some data suggest adverse events associated with PPI therapy are not seen until after 5 years of therapy 36 and this trial had a mean follow-up of 3 years and a maximum follow-up of 5 years, which was achieved in only a small proportion of patients.…”
Section: Discussionmentioning
confidence: 58%
“…This is in contrast to systematic reviews of observational studies that report the association of PPI therapy with harms such as pneumonia, 25 fracture, 26 and cerebrovascular events. 27 Biologically plausible mechanisms have been advanced to suggest these associations are causal, such as a PPI causing a change in the upper gastrointestinal tract microbiome, leading to pneumonia if aspirated 28 ; inhibition of calcium absorption leading to increased risk of fracture 29 ; and cardiovascular events may relate to PPIs reducing the activity of nitric oxide synthase. 30 A well-known maxim of epidemiology is that association is not causation 31 and these data suggest that most of these associations relate to residual confounding or biases that are inherent in observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…There was some evidence demonstrating that PPIs may not safe for long‐term use, especially in patients with CVD . For instance, a large multicenter cohort study in 2017 demonstrated that the 2‐year adjusted risk of major adverse cardiovascular events in patients taking dual antiplatelets was significantly higher in PPI users than in non‐PPI users, without a difference in bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a large multicenter cohort study in 2017 demonstrated that the 2‐year adjusted risk of major adverse cardiovascular events in patients taking dual antiplatelets was significantly higher in PPI users than in non‐PPI users, without a difference in bleeding . Furthermore, a recent meta‐analysis of observational studies in 2018 showed an increased risk of any adverse cardiovascular event in the PPI monotherapy group than in the non‐PPI group (relative risk 1.25; 95% CI 1.11–1.42; P < 0.001), independent of the use of clopidogrel; however, the result became insignificant when analyzing the data from RCTs (relative risk 0.89; 95% CI 0.34–2.33; P = 0.85) . The results are conflicting; consequently, the physicians may be reluctant to use PPIs in patients with CVD, even when those patients are not taking clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation